Jahn-Teller distortion and dissociation of CCl4+ by transient X-ray spectroscopy simultaneously at the carbon K- and chlorine L-edge. Issue 32 (2nd August 2022) - Ross, Andrew D.; Hait, Diptarka; Scutelnic, Valeriu; Haugen, Eric A.; Ridente, Enrico; Balkew, Mikias B.; Neumark, Daniel M.; Head-Gordon, Martin; Leone, Stephen R.
Abstract : Dynamics of CCl4 + prepared by 800 nm strong-field ionization, as studied with X-ray transient absorption spectroscopy (XTAS) and quantum chemical calculations. Abstract : X-ray Transient Absorption Spectroscopy (XTAS) and theoretical calculations are used to study CCl4 + prepared by 800 nm strong-field ionization. XTAS simultaneously probes atoms at the carbon K-edge (280–300 eV) and chlorine L-edge (195–220 eV). Comparison of experiment to X-ray spectra computed by orbital-optimized density functional theory (OO-DFT) indicates that after ionization, CCl4 + undergoes symmetry breaking driven by Jahn–Teller distortion away from the initial tetrahedral structure (Td ) in 6 ± 2 fs. The resultant symmetry-broken covalently bonded form subsequently separates to a noncovalently bound complex between CCl3 + and Cl over 90 ± 10 fs, which is again predicted by theory. Finally, after more than 800 fs, L-edge signals for atomic Cl are observed, indicating dissociation to free CCl3 + and Cl. The results for Jahn–Teller distortion to the symmetry-broken form of CCl4 + and formation of the Cl–CCl+3 complex characterize previously unobserved new species along the route to dissociation.